Pergeseran Pemahaman Konsep Istikharah Dari Bertanya Menuju Berserah Diri - Ansori, Ibnu Hajar (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2020)
This article is an interpretive study of Istikharah prayer taught by Rasulullah saw. as mentioned in several traditions of the Hadith. Through the content analysis method, the writer tries to analyze the meaning of the prayer analytically. From this analysis, information is obtained that there needs to be a shift in the understanding of the Istikharah concept which is generally understood as a form of 'questioning' to God about which is the best from the choices available. The intended shift - without judging the wrong of existing understanding - is towards understanding that Istikharah is the activation process of resignation. Inside is istikhÄr, istiqdÄr and istifá¸Äl. IstikhÄr is a request to be chosen the best based on Allah's Knowledge, departing from the realization that He is Omniscient while we do not know. IstiqdÄr is a request to be destined the best based on the power of God because He is the Almighty while we are not powerful. Istifá¸Äl is a request for great grace. The next process is taukÄ«l al-amr (assignment of affairs) to Allah. If good, please be destined, facilitated, and blessed. If it is bad, please turn away, destined the best, and be pleased with His destiny. The understanding will lead to the conclusion that the best answer from Istikharah is á¸¥usn al-dhann (good prejudice) to Allah and the pleasure of His qaá¸Ä -qadar.Â